THE INFLUENCE OF PROFITABILITY, FINANCIAL PERFORMANCE, AND CSR-D PRACTICES ON STOCK RETURN - Kamu, Jessica Hannah; Ekadjaja, Agustin (International Journal of Application on Economics and Business, 2025)
This study aims to analyze the impact of Return on Assets (ROA), Earnings per Share (EPS), and Corporate Social Responsibility Disclosure (CSR-D) on the stock returns of banking companies listed on the Indonesia Stock Exchange (IDX) from 2019-2023. The research employs a quantitative approach with multiple linear regression analysis with the help of microsoft excel 2016 and spss version 27. Data were obtained from the annual financial reports of banking companies from 2019 to 2023. The results indicate that ROA significantly influences stock returns, whereas EPS and CSR-D do not show a significant relationship. Therefore, investors may consider profitability aspects when making investment decisions in the banking sector. This research contributes to the understanding of fundamental factors affecting stock returns and serves as a reference for stakeholders in their investment strategies.